Visualization of evidence‐based medicine domain knowledge: production and citation of cochrane systematic reviews. Issue 1 (28th February 2013) - Shen, Jiantong; Li, Youping; Clarke, Mike; Du, Liang; Wang, Li; Zhong, Dake
Abstract: Objectives: To evaluate the production and utilization of Cochrane systematic reviews (CSRs) and to analyze its influential factors, so as to improve the capacity of translating CSRs into practice. Methods: All CSRs and protocols were retrieved from the Cochrane Library (Issue 2, 2011) and citation data were retrieved from SCI database. Citation analysis was used to analyze the situation of CSRs production and utilization. Results: CSR publication had grown from an annual average of 32 to 718 documents. Only one developing country was among the ten countries with the largest amount of publications. High‐income countries accounted for 83% of CSR publications and 90.8% of cited counts. A total 34.7% of CSRs had a cited count of 0, whereas only 0.9% had been cited more than 50 times. Highly cited CSRs were published in England, Australia, Canada, USA and other high‐income countries. The countries with a Cochrane center or a Cochrane methodology group had a greater capability of CSRs production and citing than others. The CSRs addressing the topics of diseases were more than those targeted at public health issues. There was a big gap in citations of different interventions even on the same topic. Conclusions: The capability of CSR production and utilization grew rapidly, but varied among countries and institutions, which was affected by several factors such as the capability of research, resources and the applicability of evidence. It is important to improve evidence translation through educating, training and prioritizing the problems based on real demands of end users.